PENGARUH KOMPENSASI DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN DI PT. INTI CAKRAWALA CITRA PADA INDOGROSIR KENDARI - Hendrik Irawan; Murdjani Kamaluddin; La Ode Bahana Adam; Zaluddin Zaluddin; Unika Oktaviani Damau (Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of compensation and work conflict on the performance of employees of PT Inti Cakrawala Citra Indogrosir Kendari case study. The population in this study were all employee at PT Inti Cakrawala Citra, the case study of Indogrosir Kendari, while the sample was 43 samples. Data analysis was performed using multiple linear regression analysis techniques. The results showed that compensation and work conflict had a positive and significant effect on the performance of employees of PT Inti Cakrawala Citra, the case study of Indogrosir Kendari.